2013
DOI: 10.1007/s00125-013-2904-2
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in type 1 diabetes: what is ‘double diabetes’ and what are the risks?

Abstract: In this review, we explore the concept of ‘double diabetes’, a combination of type 1 diabetes with features of insulin resistance and type 2 diabetes. After considering whether double diabetes is a useful concept, we discuss potential mechanisms of increased insulin resistance in type 1 diabetes before examining the extent to which double diabetes might increase the risk of cardiovascular disease (CVD). We then go on to consider the proposal that weight gain from intensive insulin regimens may be associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
144
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(152 citation statements)
references
References 57 publications
2
144
1
5
Order By: Relevance
“…First, T1D subjects appeared to be insulin resistant in the postprandial state and particularly during exercise, as has been observed in prior studies (4,15). This was especially relevant during exercise, when both plasma insulin and glucose concentrations were higher in T1D than healthy subjects.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…First, T1D subjects appeared to be insulin resistant in the postprandial state and particularly during exercise, as has been observed in prior studies (4,15). This was especially relevant during exercise, when both plasma insulin and glucose concentrations were higher in T1D than healthy subjects.…”
Section: Discussionsupporting
confidence: 51%
“…Further analyses of the data obtained in this study in T1D subjects and comparison with those obtained in healthy nondiabetic subjects undergoing a similar exercise protocol reported recently (25) have provided several striking differences discussed below. Fasting glucose concentrations were significantly higher despite higher fasting insulin concentrations in T1D than in healthy subjects, implying that insulin resistance in T1D subjects in the baseline rested state as has been demonstrated before (4,15). Detailed examination of the concentration profiles of the underlying hormones (insulin and glucagon) provides interesting perspectives and differences.…”
Section: Discussionmentioning
confidence: 90%
“…HDL-C values are generally similar or even higher in patients with type 1 diabetes compared with the general population (10). The higher HDL-C concentrations can partly be explained by the subcutaneous insulin administration, which enhances lipoprotein lipase and is associated with an improved lipid profile (26,27). However, whether or not the functionality and protective effect of HDL-C are similar in patients with type 1 diabetes compared with that of the general population has been questioned (28).…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of double diabetes (i.e., when patients with type 1 diabetes show features of insulin resistance and type 2 diabetes) is increasing due to the societal trend of increased adiposity as well as weight gain caused by intensive glycemic control (27). Furthermore, the subcutaneous insulin administration leads to relative peripheral hyperinsulinemia and hepatic hypoinsulinemia, and a chronic adaption to this could reduce peripheral insulin uptake and increase hepatic glucose production, inducing insulin resistance (27). We have previously shown that in the FinnDiane population of type 1 diabetes, the overall prevalence of metabolic syndrome was 38% in men and 40% in women (36).…”
Section: Resultsmentioning
confidence: 99%
“…A significant relationship exists between mortality and central obesity in those with type 1 diabetes [20] and type 1 subjects with the MetS have been shown to have an increased prevalence of macrovascular disease [29] . The presence of MetS features in patients with type 1 diabetes is associated with risk factors similar to many patients with type 2 diabetes, and the superimposition of the insulin resistance due to obesity or the MetS in a patient who already has type 1 diabetes has been termed "Double diabetes" [30] . Identifying patients with the MetS in the presence of type 1 diabetes is difficult.…”
Section: Type 1 Diabetes and The Metabolic Syndromementioning
confidence: 99%